Association of serum soluble urokinase receptor levels with progression of kidney disease in children - Schaefer, Franz; Trachtman, Howard; Wühl, Elke; Kirchner, Marietta (JAMA pediatrics, 2017)
Importance: Conventional methods to diagnose and monitor chronic kidney disease (CKD) in children, such as creatinine level and cystatin C–derived estimated glomerular filtration rate (eGFR) and assessment of proteinuria in spot or timed urine samples, are of limited value in identifying patients at risk of progressive kidney function loss. Serum soluble urokinase receptor (suPAR) levels strongly predict incident CKD stage 3 in adults. Objective; To determine whether elevated suPAR levels are associated with renal disease progression in children with CKD. Conclusions and Relevance: Patients with high suPAR levels were more likely to have progression of their kidney disease. Further studies should determine whether suPAR levels can identify children at risk for future CKD.
Published Online: September 5, 2017
Gesehen am 12.09.2018